Functional characterization of two newly identified Human Endogenous Retrovirus coding envelope genes - Blaise, Sandra (BioMed Central, 2005)
A recent in silico search for coding sequences of retroviral origin present in the human genome has unraveled two new envelope genes that add to the 16 genes previously identified. A systematic search among the latter for a fusogenic activity had led to the identification of two bona fide genes, named syncytin-1 and syncytin-2, most probably co-opted by primate genomes for a placental function related to the formation of the syncytiotrophoblast by cell-cell fusion. Here, we show that one of the newly identified envelope gene, named envP(b), is fusogenic in an ex vivo assay, but that its expression – as quantified by real-time RT-PCR on a large panel of human tissues – is ubiquitous, albeit with a rather low value in most tissues. Conversely, the second envelope gene, named envV, discloses a placenta-specific expression, but is not fusogenic in any of the cells tested. Altogether, these results suggest that at least one of these env genes may play a role in placentation, but most probably through a process different from that of the two previously identified syncytins.